Implementasi Akuntansi Biaya pada Perhitungan Harga Jual Produk Komunitas Cemal Cemil Corner - Rahmasari Fahria; Husnah Nur Laela Ermaya; Ayunita A.S Mashuri (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This activity aims to help SMEs community Cemal Cemil Corner identify, classify, and calculate costs by applying cost accounting techniques so that the community is able to calculate costs, selling price, and optimal profits more accurately as well as break-event point calculations. This activity is using educational method in the form of counselling and assistance to the community. This activity focuses on educating the implementation of cost accounting techniques in calculating business costs and determining product selling prices. The result of this activity is this community able to implement cost accounting techniques in determining product cost, selling price and to calculate break-event point more accurately.